The role of MAPT sequence variation in mechanisms of disease susceptibility. - Caffrey, T; Wade-Martins, R (2012)
The microtubule-associated protein tau (MAPT or tau) is of great interest in the field of neurodegeneration as there is a well-established genetic link between the MAPT gene locus and tauopathies, a diverse group of neurodegenerative dementias and movement disorders. The genomic architecture in the region spanning the MAPT locus contains a ~1.8 Mb block of linkage disequilibrium characterized by two major haplotypes: H1 and H2. Recent studies have established strong genetic association between the MAPT locus and neurodegenerative disease and uncovered haplotype-specific differences in expression and alternative splicing of MAPT transcripts. Integrating genetic association data and gene expression data to understand how non-coding genetic variation at a gene locus affects gene expression and leads to susceptibility to disease is a high priority in disease genetics, and the MAPT locus provides an excellent paradigm for this. In the absence of protein-coding changes caused by haplotype sequence variation, altered levels of protein expression or altered ratios of isoform expression are excellent candidate mechanisms to link the MAPT genetic disease association with biological function. The use of novel transgenic and endogenous genetic models are required to understand the role of MAPT sequence variation in mechanisms of disease susceptibility.